An Attempt to Apply Analogs of the Dubinin-Radushkevich and Freundlich Equations for Describing Isotherms of Adsorption from Binary Liquid Solutions of Non-Electrolytes with Unlimited Miscibility - J.K. Garbacz; S. Biniak; P. Cysewski (Adsorption Science & Technology, 1987)
An extention of the Dabrowski and Jaroniec concept of describing adsorption from binary liquid solutions of non-electrolytes on solids in terms of the Dubinin-Radushkevich (DR) and Freundlich (F) equations is presented. A new solution has been advanced based on the definition of the chemical affinity of the process of generation of equilibrium bulk phase from the pure components of the solution. The real adsorption isotherm equation has been formulated in which particular cases are the quasi-DR equation and the quasi-F equation. Some adsorption systems are described.